2017
DOI: 10.1371/journal.ppat.1006237
|View full text |Cite
|
Sign up to set email alerts
|

Nematode neuropeptides as transgenic nematicides

Abstract: Plant parasitic nematodes (PPNs) seriously threaten global food security. Conventionally an integrated approach to PPN management has relied heavily on carbamate, organophosphate and fumigant nematicides which are now being withdrawn over environmental health and safety concerns. This progressive withdrawal has left a significant shortcoming in our ability to manage these economically important parasites, and highlights the need for novel and robust control methods. Nematodes can assimilate exogenous peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 67 publications
3
34
0
1
Order By: Relevance
“…VOCs kill nematodes by mechanisms that can affect the nervous system 28 , surface coat, intestine 8 , pharynx, or other tissues. Vacuoles were observed in the intestine of M .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VOCs kill nematodes by mechanisms that can affect the nervous system 28 , surface coat, intestine 8 , pharynx, or other tissues. Vacuoles were observed in the intestine of M .…”
Section: Resultsmentioning
confidence: 99%
“…That PPNs locate their plant hosts by chemoreception was proposed over 90 years ago 23 , and has since been demonstrated in vitro by chemotaxis assays on agar-filled dishes 24 – 27 . It has been suggested that the use of some compounds like neuropeptides to control nematode behavior might be an efficient way to reduce the infection levels of PPNs 28 . We hypothesize that a similar approach based on VOCS with which PPNs have a stable chemotactic response might also serve as a novel nematicidal mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…rostochiensis, G. pallida and M. incognita and M. graminicola (Atkinson et al, 1988;Maule et al, 2002;McVeigh et al, 2005;Kimber et al, 2007;Dalzell et al, 2010;Holden-Dye and Walker, 2011;Atkinson L. E. et al, 2013;Papolu et al, 2013;McCoy et al, 2014;Kumari et al, 2017;Warnock et al, 2017). So far, nineteen FLPs have been identified in the M. incognita and out of which six have been established to have transcriptional evidence (Abad et al, 2008) and host-delivered RNAi of Mi-flp14 and Mi-flp18 in N. tabacum provided excellent reduction in nematode parasitism and reproductive potential (Papolu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…神经肽样蛋白(neuropeptide-like protein, NLP)代 表研究最少的神经肽分组, 根据Warnock等人 [90] [69,91] . PF-127已广泛应用于植物寄生线虫与 植物的互作关系研究 [92] .…”
Section: 键基因 根据生物信息学分析 预测Flp-1在神经肽信unclassified